Prediction of the mesiodistal width of maxillary anterior teeth from nasal interalar width in peruvian subjects with facial harmony - Valerie Saldaña-Carranza; Marcos J. Carruitero (Universidad de Concepción., 2020)
Objective: To determine regression models to predict the mesiodistal widths of the maxillary anterior teeth from interalar width of the nose in subjects with facial harmony. Materials and Methods: A cross-sectional study was carried out in a sample of 75 subjects with facial harmony and ages ranging from 18 to 30 years (21.28±3.75 years). The mesiodistal width of the central (CI), lateral (LI) incisors, and canines (C), as well as the interalar width (IW) of each subject were measured using a digital vernier caliper. Simple linear regression analyses were used to predict the width of the maxillary anterior teeth from the nasal interalar width, from which formulas for predicting the dimensions of each anterior tooth were obtained. Results: A statistically significant relationship was found between the nasal interalar width and the mesiodistal widths of the upper central incisor (p=0.019, R2=5.23%), upper lateral incisor (p=0.019, R2=2.31%), and upper canine (p=0.016, R2=12.04%) that allowed to develop simple linear prediction models for each tooth represented by the following formulas: CI=7.04+0.04(IW); LI=6.01+0.03 (IW); C=6.19+0.05 (IW). Conclusion: The nasal interalar width is a good predictor of the mesiodistal widths of the maxillary anterior teeth.